Dystopian and Utopian Omission of Discourse in Three Modern Robinsonades: Lord of the Flies, Concrete Island, The Red Turtle - Gill, Patrick (Porównania, 2019)
The story of Robinson Crusoe comes to us in the guise of a first-person narrative based in part on a diary. Successor texts have traditionally adopted the same narrative situation, exploiting it in order to foreground ideas of authorship, textual authority and linguistic dominance. This essay pays particularly close attention to those Robinsonades that have not followed this pattern and have instead opted to omit meta-narration and intradiegetic narrator figures. It considers to what ends this is done in three modern Robinsonades: William Golding’s Lord of the Flies (1954), J. G. Ballard’s Concrete Island (1974), and Michael Dudok de Wit’s animated film The Red Turtle (2016).